Prevalence of Osteoporosis in Women Over 50 Years of Age: Preventive and Therapeutic Management Skills - Enrique Rodríguez Reyes; Carlos Alberto Valverde González; Walter Alberto Vayas Valdiviezo (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Foundation: osteoporosis is a disease that causes the loss of bone mass and the weakening of bone tissue, which causes an increased risk of fractures. It is important to educate the population, prevent and detect the disease early and combat risk factors. Objective: to analyze the prevalence and evaluate the level of knowledge about osteoporosis in women over 50 years of age and the ability to apply this knowledge in the prevention and treatment of this pathological entity. Methods: a study with a cross-sectional, non-experimental and field design was carried out. The study material consisted of a sample of 103 women over 50 years of age that corresponded to the population that attended consultation at the Center for Specialties in Rheumatology and Immunology, for various reasons, between January and May 2023. To verify the data, used a diagnostic survey method and a questionnaire constructed for the purposes of this study and validated by center experts. The declared variables were subjected to statistical analysis to determine characteristics of the sample and correlation between the variables. The verification of the hypothesis was based on the Chi-square test. For significant points, a normalization of the coefficient using Cramer's V coefficient was included. Results: among the women surveyed and their relatives, 20 % suffered from osteoporosis. Among the predisposing and causing factors of osteoporosis in the study group were poor diet and lack of exercise. 48 % knew the meaning of the densitometry test, the use of all necessary ingredients in the diet was confirmed by 36 % of women, the use of pharmacological preparations for calcium supplementation was reported by only 33 % of women. Conclusions: the level of knowledge of women about osteoporosis is insufficient and does not allow them to adopt preventive or curative measures. Among the predisposing and causing factors of osteoporosis are poor diet and lack of exercise.